Reflection of Identity Through the Use of Bintil Language in the Community Gaya Lentera Muda Lampung - Oktora, Imelda; Kartika, Tina (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2017)
Effeminate man is a unique form of life for most of people. Effeminate language reflects the effeminate characters which is sensitive because basically effeminate men are creative people. Therefore, the effeminate language represents the creativity forms of language as slang words which are fascinating, brief, and recall simply. This research aim is to describe the difference of verbal and nonverbal language usage among Effeminate Men, Gay, and LSL in Gaylam Community. This research method used descriptive kualitative method and Symbolic Interaction Theory as research analysis theory. This research found the difference among Gay, Effeminate Men, and LSL is only at their intonation when they are stating the language. Because through the intonation it can give their own intention to theirself and there are 42 words examples which are usually used in community, likes: Eke Senandung sama Kanua, Apa kabose, Banjaran, Benyong, Bodrek, Barbie, Pepsi/Kencana wungu, Centong, Capcus, Dese, Duta, Endul/Endang, Gedung, Gilda/Gilingan, Hitachi/Puput melati, Greton/Gretongan, Inang, Eim/Ember/Um, Jalinan kasih, Jengong, Lagi apose, Lapangan bola, Lekong/Laksa, Lambreta, Lupus, Maharani/Mehong, Makarena/Mekong, Malay, Mandala, Maram/Murka/Merong, Mawar kemandul, Mebra/Motorola, Pecongan, Pereâ/Pewong /Racun, Polo/Polda, Puyung hai/Peniti/Puspa, Sepiring/Sepoi, Sindang, Sirsak, Tinta dan Tandus.